Muscle activation during side-step cutting maneuvers in male and female soccer athletes - Hanson, A. M.; Padua, D. A.; Blackburn, J. T.; Prentice, W. E.; Hirth, C. J. (Journal of Athletic Training, 2008)
Female soccer athletes are at greater risk of anterior cruciate ligament (ACL) injury than males. Sex differences in muscle activation may contribute to the increased incidence of ACL injuries in female soccer athletes.